MUERTE ACCIDENTAL DE Stenocercus ornatissimus POR ATASCAMIENTO EN EL ANILLO DE UNA LATA DE LECHE: UN CASO DE AMENAZA NO DOCUMENTADA PARA PERÚ - Choy Pravatiner, Manuel (2025)
Remains of an individual of Stenocercus ornatissimus were found on the trail between the districts of San Damián and Antioquia in the province of Lima, Peru, in 2023. The remains indicated that the individual became trapped in the ring of a milk can while attempting to enter it. Such an event has never been reported for this species, nor for any other lizard species in this country. This finding highlights a potential threat to the population of S. ornatissimus, which is already considered near threatened and declining.